2015
DOI: 10.5604/15093492.1193035
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after Open Reduction and Plate Fixation of Distal Humerus Fractures

Abstract: Open reduction and internal fixation using two perpendicular plates allows for achieving good stability of fixation, early rehabilitation and quick return to the desired level of activity, which contributes to a high percentage of good objective and subjective results of treatment. Subjective assessment of upper limb function after DHF surgery fully correlates with objective assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…7 DASH score and range of motion is used to access stiffness of elbow joint. 9 Study by Holub et al showed in study of 41 patients, non-union rate of 5%, union rate of 95%. 10 Complications includes joint stiffness, ulnar neuropathy, post traumatic arthritis, osteonecrosis and symptomatic hardware.…”
Section: Introductionmentioning
confidence: 94%
“…7 DASH score and range of motion is used to access stiffness of elbow joint. 9 Study by Holub et al showed in study of 41 patients, non-union rate of 5%, union rate of 95%. 10 Complications includes joint stiffness, ulnar neuropathy, post traumatic arthritis, osteonecrosis and symptomatic hardware.…”
Section: Introductionmentioning
confidence: 94%